(untitled) (Research, Society and Development, 2022)
Removal of third molar components is the most common procedure performed in everyday practice in oral surgery. In all surgical procedures, proper and planned surgical procedures from preoperative techniques to surgical procedures, to lessen the difficulty of complications. Third molar removal is no different, but such a common procedure sometimes does not result in rare complications. In this study, this study will review the literature on accidents and complications related to third-party extractions, as well as define the most appropriate procedure to be performed in these situations. For the construction of this article, a bibliographic survey was carried out in the SciVerse Scopus, Scientific Electronic Library Online (Scielo), U.S. National Library of Medicine (PUBMED) and ScienceDirect databases, with the help of the Mendeley reference manager. The articles were included between the years 2010 to 2021. Surgical complications for third molar extractions can be classified as simple, such as dental fractures, small oro-sinus communications and ration of flaps and more serious complications that often have specialized treatment, such as oral-sinus communications, of instruments with total penetration into the tissues, as in some cases of needle fractures, trans-surgical mandibular fractures and others in cases of trans-surgical mandibular fractures, such as cases of nerve fractures. The prevention of complications should be the main objective of surgeons and a detailed information related to the knowledge of professionals are fundamental factors. The more complex the techniques in which osteotomy and odontosection are required, the greater the chance of postoperative complications, such as alveolitis, trismus and paresthesia, requiring more professionals.